Major hepatectomy decreased tumor growth in an experimental model of bilobar liver metastasis. Issue 10 (October 2020) - Schwarz, Lilian; Nicol, Lionel; Francois, Arnaud; Mulder, Paul; Faitot, François; Dazza, Marie; Bucur, Petru; Savoye-Collet, Céline; Adam, René; Vibert, Eric
Abstract: Background/Purpose: Two-stage hepatectomy (TSH), is associated with a risk of drop-out due to tumoral progression following portal vein occlusion (PVO). We explored the impact of majorhepatectomy on tumor growth by objective radiological measures comparing to PVO and minor hepatectomy, using a model of bilobar colorectal liver metastasis (CLM). Methods: CLM were induced in 48 BDIX rats by injection of DHDK12-cells. 7 days after cells injection, animals were distributed into 4 groups of equal number (n = 12): portal vein ligation (PVL), sham laparotomy (sham), minor (30%Phx) and major (70%Phx) hepatectomy. MR imaging was used for in vivo analysis of tumor implantation, growth and volumes. Results: At POD10, tumour volumes were homogeneously distributed among the 4 groups. Lower TV were significantly observed after 70%Phx comparing to PVL at POD17 (0.63 ± 0.14cm3 vs 0.9 ± 0.16cm3, p = 0.008) and to the 3 others groups at POD24: 1.78 ± 0.38cm3 vs 3.2 ± 0.62cm3 (PVL, p = 0.019), 2.41 ± 0.74cm3 (Sham, p = 0.024) and 2.32 ± 0.59cm3 (30%PHx, p = 0.019). Conclusion: We confirmed in a reproducible model that contrary to PVO, a major hepatectomy decreases the growth of CLM in the remnant liver. This result leads to questioning the usual TSH and justifies exploring alternative strategies. The "major hepatectomy first-approach" should be an option to be evaluated.